SHORT COMMUNICATION: COVID-19 Pandemic and Attitude of Citizens in Bandung City Indonesia (Case Study in Cibiru Subdistrict) - Sumaryana, Asep; Toharudin, Toni; Eko Caraka, Rezzy; Septiani Pontoh, Resa; Ching Chen, Rung; Pardamean, Bens (International Journal of Criminology and Sociology, 2022)
In the beginning, the pandemic panicked the people of Cibiru. Over time, the case fell in line with the increasing number of patients recovering. In addition, different views between elements of government make people surrender and believe in the power of nature’s creator. Under these conditions, the researchers were interested in learning more. The study was conducted using a descriptive analysis of a number of parties regarding economic and social activities. The results show that there are three important components: First, trust builds the creator and reduces to the government component, communication that a number of parties do not work consistently when responding to COVID-19, and enforcement of unclear rules. In a nutshell. The citizens, grouped into two groups, agree that a pandemic is dangerous and urge them to follow values in the form of existing rules. Also,The pandemic communication competes in a short time and therefore cannot be carried out interactively.The government’s assertiveness of forcing residents to be at home becomes difficult as compensation can be granted for lost opportunities to seek family income Lastly, due to the preparation of the strategy that precedes the arrival of a pandemic, it cannot be face wisely.